Pengelolaan Keuangan pada UMKM di Desa Dawuhan Kecamatan Wanayasa Kabupaten Banjarnegara - Astohar Astohar; Emi Wardati; Sugiharti Sugiharti; Andriana Olo (Pusat Riset dan Inovasi Nasional, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Dawuhan Village, Wanayasa District have experienced quantitative development. Differences occur in MSMEs that consistently make financial reports, especially micro and small businesses that are not in line with quantitative developments. MSMEs in Dawuhan Village do not routinely report MSME performance (operational and financial) so that financial conditions cannot be known early by MSME owners. Lecture, discussion, simulation and question and answer methods regarding the benefits and uses of preparing reports were chosen for delivering the material. The results of the community service show that actions are still needed to convince MSMEs regarding the importance of financial reports. Several participants were able to understand and were enthusiastic about participating in the training. In the future, training and introduction of financial applications related to MSMEs such as Buku Warung, Siapik or other applications are needed. The role of the Banjarnegara Regency Government apparatus (related agencies) through Dharma Wanita, Pokdarwis or Karang Taruna (youth groups) needs to be improved.